1997
DOI: 10.1002/sca.4950190408
|View full text |Cite
|
Sign up to set email alerts
|

World wide web‐controlled scanning electron microscope

Abstract: Summary: This paper 1 presents a system for remote control of a scanning electron microscope (SEM) over the Internet using the World Wide Web (WWW). The evolution of the SEM to its current incarnation as a PC-SEM is noted, and the World Wide Web is briefly described. The implementation of the authors' system is detailed in terms of configuration and manner of interaction. The potential commercial applications of the research are described. Related work in microscopy and networking fields is considered. A discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…As web technologies were booming and achieving more improvements than other distributed computing technologies, global manufacturing systems became possible and received more attentions than ever. Chand et al [4] have developed a webbased scanning electron microscope system, which enabled an operator to adjust the scanning electron microscope's parameters via web. The scanning system was deployed in Microsoft Windows™ operating system and CGI (Common Gateway Interface) was used to receive and send static data, such as string, file, and image.…”
Section: Introductionmentioning
confidence: 99%
“…As web technologies were booming and achieving more improvements than other distributed computing technologies, global manufacturing systems became possible and received more attentions than ever. Chand et al [4] have developed a webbased scanning electron microscope system, which enabled an operator to adjust the scanning electron microscope's parameters via web. The scanning system was deployed in Microsoft Windows™ operating system and CGI (Common Gateway Interface) was used to receive and send static data, such as string, file, and image.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimentation with scanning electron microscopes (SEM) showed that information such as images, X-ray spectra and parameter data could be shared among geographically dispersed investigators in real time through the Internet Chand et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The success of this classroom was widely disseminated and the rapid development of remote-control computerbased microscopes began. A Philips XL30 microscope was adapted at the University of Michigan to allow remote operation on campus using PC Anywhere (URL: http://apps.internet2.edu//demos97/sem.htm) while developments by researchers at LEO (Chand et al, 1996(Chand et al, , 1997 demonstrated that remote operation using the Java language and the worldwide web was feasible. Within a short time all microscope companies were advertising remote-control features of some sort, often using a combination of third-party software such as CU-SeeMe, PC Anywhere, or Microsoft's Net-Meeting.…”
Section: Introductionmentioning
confidence: 99%